Fatigue induced deformation and thermodynamics evolution in a nano particle strengthened nickel base superalloy. Issue 6 (11th February 2016) - Huang, E‐W.; Chang, C.‐K.; Liaw, P. K.; Suei, T.‐R.
Abstract: In‐situ neutron‐diffraction and temperature measurements were simultaneously applied to investigate low‐cycle‐fatigue behaviour of a nano‐precipitate strengthened nickel‐based superalloy. Two transitions in the temperature‐evolution are observed subjected to cyclic loading. Two models are compared with the measured temperature evolution. One is based on bulk stress, and the other is based on lattice‐strain evolution. The calculated thermoelastic responses in both models qualitatively agree with the measured bulk‐temperature evolution for the first transition. The in‐situ neutron‐diffraction results reveal that the first transition is associated with the cyclic hardening/softening dislocation‐structural transformation. However, the second transition, which is observed at larger number of fatigue cycles during the steady cycles, does not correlate with the dislocation evolution. A phenomenological model is applied to describe the second temperature‐transition stages. The energy dissipation evolutions in the second fatigue stage indicate the initiation and the growth activities of fatigue microcrack. The data reported here may be useful for cohesive zone model.